# How do you find the average rate of change of #y=x^2-x+1# over [0,3]?

The average rate of change of function

By signing up, you agree to our Terms of Service and Privacy Policy

To find the average rate of change of ( y = x^2 - x + 1 ) over the interval [0,3], you first need to calculate the values of the function at the endpoints of the interval, which are ( x = 0 ) and ( x = 3 ). Then, find the difference in the values of the function at these endpoints, and divide this difference by the difference in the corresponding values of ( x ), which is ( 3 - 0 = 3 ). This gives you the average rate of change of the function over the interval [0,3].

Substitute ( x = 0 ) and ( x = 3 ) into the function: ( y(0) = (0)^2 - 0 + 1 = 1 ) ( y(3) = (3)^2 - 3 + 1 = 7 )

The difference in the values of the function at the endpoints is: ( 7 - 1 = 6 )

The difference in the values of ( x ) at the endpoints is: ( 3 - 0 = 3 )

Therefore, the average rate of change of the function over the interval [0,3] is: ( \frac{6}{3} = 2 )

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the equation of the tangent line to the curve #y=2xsinx# at #(pi/2,pi)#?
- How do you use the limit definition of the derivative to find the derivative of #f(x)=(x+1)/(x-4)#?
- What is the equation of the line that is normal to #f(x)= e^(2x-2) /sqrt( 2x-2) # at # x=3 #?
- What is the equation of the tangent line of #f(x) =x^2-sqrt((3x^2-9x)/(x+6))# at # x = 3#?
- At what point on the curve #y=1+2e^x-3x# is the tangent line parallel to the line #3x-y=5#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7